Physiologic Anchorage Control A New Orthodontic Concept and its Clinical Application - Xu, Tian Min.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive introduction to physiologic anchorage control, explains the implications for clinical practice, and presents an anchorage technique applicable for the treatment of different malocclusions. The concept of physiologic anchorage control is derived from observations of upper molar movement during growth in adolescence, including in the absence of orthodontic treatment, which indicate that molar forward displacement comprises two components: the first due to biologic force or physiologic anchorage loss and the second due to orthodontic force or mechanical anchorage loss. All previous anchorage methods have been based on the assumption that molar anchorage loss is to be attributed solely to the mechanical force used to retract anterior teeth, and the new concept represents a paradigm shift of clinical significance. This book explores the pattern of upper molar growth in depth, highlights the physiologic significance of the curve of Spee, and analyzes the biomechanics of physiologic anchorage control. An anchorage control system that fully takes into account the latest conceptual insights is described and its clinical use and utility, examined.
A Brief Overview of Orthodontic Anchorage -- Concept of Physiologic Anchorage Loss -- Pattern of Upper Molar Growth -- Impact of Straight Arch Wire on Individual Molar Angulation -- Biomechanics of Physiologic Anchorage Control -- Pro and Con of Light Force Low Friction Appliance -- Physiologic Anchorage Spee-archwire System -- Clinical Application of Physiologic Anchorage Control System.
Keywords: Dentistry; Dentistry; Dentistry